A Comparative Study of the General Health among Staff Nurses with Fixed or Rotating Working Shift - M .A. Soleimany; F. Nasiri-ziba; A. Kermani; F. hoseini (Iran University of Medical Sciences, 2007)
Introduction and Aim: Long time working shifts and its related tiredness threatens the health of staff nurses in various dimensions. If nurses don't experience a good general health, they would not be able to deliver good patient care. The health status of nurses as caregivers influences the quality of care received by patients. Therefore, in order to reach the point of maximum performance, it is necessary for nurses to be healthy. This study aims to compare the general health among two groups of staff nurses with either fixed or rotating working shift in educational health care centers of Iran University of Medical Sciences in year 2006.Materials and Methods: This comparative study was conducted with a sample of 520 nurses. A GHQ-28 tool was used to survey the general health of staff nurses participated in this study.Results: The findings showed that 72.3% of nurses with fixed working shift had good general health, 18.8% had nearly good general health and 8.8% had bad general health. Of nurses with rotating working shift, 62.3% had good general health, 26.2% had nearly good general health, and 11.5% had bad general health. The results of Chi-Square test showed a statistically significant difference in general health of nurses with fixed working shift compared with nurses with rotating working shift, indicating that the nurses with fixed working shift have better general health (P < 0.005).Conclusion: Because nurses are responsible for society and patient's health taking their general health into consideration is of great importance. Based on findings of the present study, the researchers recommend the nurse managers to plan staff schedules in the form of fixed working shifts, in order to minimize untoward influences of rotating working shifts.